Solution‐Processed, Self‐Powered Broadband CH3NH3PbI3 Photodetectors Driven by Asymmetric Electrodes. Issue 15 (14th May 2020) - Perumal Veeramalai, Chandrasekar; Yang, Shengyi; Zhi, Ruonan; Sulaman, Muhammad; Saleem, Muhammad Imran; Cui, Yanyan; Tang, Yi; Jiang, Yurong; Tang, Libin; Zou, Bingsuo
Abstract: In general, the fabrication of high‐performance, self‐powered broadband photodetectors based on traditional semiconducting thin films is tedious and costly. Here, in this paper a high‐performance, solution‐processed, and self‐powered CH3 NH3 PbI3 (MAPbI3 ) nanocrystal based photodetector ITO/MAPbI3 /Ag is presented, and it shows broadband photoresponse from the visible to the near‐infrared wavelength region. The pronounced enhanced performance of the photodetector is due to taking the advantage of the built‐in electric field induced by the work function difference of two electrodes. The optimized photodetector shows a responsivity of 4.9 and 1.42 A W −1 with a specific detectivity of 7.6 × 10 13 and 1.77 × 10 13 Jones under 19 µW cm −2 white light illumination and 26 µW cm −2 808 nm illumination at zero bias, respectively. Therefore, such a concept of simple device geometry and feasible technique will open up a new and promising avenue for the fabrication of self‐powered photodetectors and the development of imaging devices. Abstract : Colloidal CH3 NH3 PbI3 nanocrystals are synthesized by ligand‐assisted reprecipitation combined with ultrasonication, and their application in self‐powered broadband photodetector ITO/CH3 NH3 PbI3 /Ag is presented, showing a responsivity of 4.9 and 1.42 A W −1 with a specific detectivity of 7.6 × 10 13 and 1.77 × 10 13 Jones under 19 µW cm −2 white light illumination and 26 µW cm −2 808 nm illumination at zero bias, respectively.